«I Wanted to Prove that I Can Make Trend». Online Citizen Activisms and ‘Poplitical’ Practices in Peru - Castro Pérez, Raúl (2019)
During the last decade, the way social media is structuring contemporary political participation and citizen mobilization was been discussed. Studies focus on the raising interactivity that platforms like Facebook, YouTube or Twitter facilitate, as well as massive protest and activism that emerge from them, in sinergy with square and street movements. Studies refer to episodic activisms that target banal goals and have no formal militance in political parties, exercising actions against arbitrary decisions of everyday power.May these mobilizations, and their expressive repertoires, like performances and media strategies, be labelled as poplitic practices? The present article uses that concept as an interpretive model for the analysis of two Peruvian case studies: Meme No and Alerta contra policías con cámaras de velocidad («Alert of Police with Speed Cameras»). In the search for the digital storytelling of their activists, and in the content analysis of their resources, like memes and viral processes, the present article will dimension the actual height of mobilizations.